The Evolution of Vocational Undergraduate Education in Policy Discourse: From “Level Extension” to an “Independent Type” - Zhu, Wei; Ouyang, Ping; Ke, Xue (Journal of Research in Vocational Education, 2025)
With the adjustment of China’s industrial structure and the rise of the digital economy, vocational undergraduate education has emerged as a vital pathway for cultivating high-level technical and skilled talent. However, existing research has paid limited attention to the conceptual evolution of vocational undergraduate education as shaped by shifting policy discourse. This paper analyzes the transformation of policy narratives surrounding vocational undergraduate education, tracing how it has evolved from being viewed as a “level extension” of higher vocational education to an “independent type” within the higher education system. The study explores how policy, socio-economic demands, and changing educational philosophies have jointly driven this conceptual shift and the internal development of the vocational undergraduate model. Through case studies, the paper further illustrates how national and local policies have supported the reform and innovation of vocational undergraduate education in practice-particularly in refining talent cultivation goals, enhancing curriculum design, and strengthening industry-education integration. Based on these findings, the paper offers policy recommendations to promote the continued development of vocational undergraduate education, aiming to provide a theoretical foundation and practical guidance for its sustained innovation and optimization.